Age but not vitamin D is related to sarcopenia in vitamin D sufficient male elderly in rural China - Weinuo Mi; Huifeng Zhang; Lina Zhang; Xingjia Li; Zhiguo Wang; Yu Sun; Tonggao Shen; Kuanlu Fan; Chao Liu; Shuhang Xu (Scientific Reports)
Abstract This study aimed to identify the correlation of serum 25(OH)D level with sarcopenia and its components in Chinese elderly aged 65 years and above from rural areas. A total of 368 Chinese elderly aged 65 years and above in rural areas were enrolled. Indicators of muscle mass and strength, including the appendicular skeletal muscle mass (ASM), skeletal muscle index (SMI) and hand grip strength (HGS) were measured. Physical performance was assessed by the Short Physical Performance Battery (SPPB). Serum 25(OH)D levels were measured using the liquid chromatography with tandem mass spectrometry. Correlations of serum 25(OH)D level with sarcopenia and its components in Chinese elderly were identified by the binary logistic regression and linear regression analyses. The median serum 25(OH)D level was 34.80 ng/ml, and significantly higher in men than in women (40.70 ng/ml vs. 27.30 ng/ml). The prevalence of sarcopenia in our cohort was 21.5%, and higher in men than in women (29.4% vs. 10.8%). The serum 25(OH)D level was not correlated with sarcopenia, HGS and SPPB score in either male or female elderly. Positive correlations of age with sarcopenia, low HGS and low SPPB score were observed in male elderly, while significant correlations were not observed in females. Correlation analyses of sarcopenia components revealed that age was negatively correlated with SMI and gait speed in male elderly, but negatively correlated with the gait speed and positively correlated with the time to complete 5 sit-to-stand movements in female elderly. In conclusion, rural Chinese elderly have relatively high vitamin D level and prevalence of sarcopenia. Age but not serum 25(OH)D level is significantly correlated with sarcopenia in vitamin D sufficient male elderly.